Primary Amebic Meningoencephalitis Caused by Naegleria fowleri, Karachi, Pakistan - Shakoor, Sadia (Centers for Disease Control and Prevention, 2011)
We report 13 cases of Naegleria fowleri primary amebic meningoencephalitis in persons in Karachi, Pakistan, who had no history of aquatic activities. Infection likely occurred through ablution with tap water. An increase in primary amebic meningoencephalitis cases may be attributed to rising temperatures, reduced levels of chlorine in potable water, or deteriorating water distribution systems.